2015
DOI: 10.1113/jp270211
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle mitochondrial H2O2 emission increases with immobilization and decreases after aerobic training in young and older men

Abstract: Key pointsr Currently, it is not known whether impaired mitochondrial function contributes to human ageing or whether potential impairments in mitochondrial function with age are secondary to physical inactivity.r The present study investigated mitochondrial respiratory function and reactive oxygen species emission at a predefined membrane potential in young and older men subjected to 2 weeks of one-leg immobilization followed by 6 weeks of aerobic cycle training.r Immobilization increased reactive oxygen spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 54 publications
4
62
3
Order By: Relevance
“…In humans, chronic exercise caused similar increases in antioxidant capacities and reduced ROS damage, and one of the recognised benefits of regular exercise is that it reduces oxidative stress (Gram et al, 2015;Radak et al, 2013). Our results indicate that the transfer of the increased antioxidant capacity to improve resilience to the negative effects of UV-B radiation is an additional benefit of regular exercise beyond its direct health-promoting effects (Booth et al, 2012;Hawley and Holloszy, 2009;Joseph et al, 2016).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In humans, chronic exercise caused similar increases in antioxidant capacities and reduced ROS damage, and one of the recognised benefits of regular exercise is that it reduces oxidative stress (Gram et al, 2015;Radak et al, 2013). Our results indicate that the transfer of the increased antioxidant capacity to improve resilience to the negative effects of UV-B radiation is an additional benefit of regular exercise beyond its direct health-promoting effects (Booth et al, 2012;Hawley and Holloszy, 2009;Joseph et al, 2016).…”
Section: Discussionmentioning
confidence: 56%
“…Physical activity increases ROS production by contracting muscle acutely (Powers and Jackson, 2008). However, chronic low-to midlevel physical activity (exercise) increases antioxidant defences, such that oxidative stress is reduced with chronic exercise (Gram et al, 2015;Radak et al, 2013). Defences against oxidative stress in muscle include enzymatic antioxidants like superoxide dismutase (SOD) and catalase (CAT), and non-enzymatic ROS scavengers such as glutathione (GSH; Sen, 1995;Steinbacher and Eckl, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria contributes to muscle ROS production during immobilization [52, [54][55][56], but other studies highlight that XO plays also an important role [57,58]. To the best of our knowledge no studies reported that NOX, NOS or ER plays a role in the production of ROS induced by immobilization.…”
Section: Skeletal Muscle Oxidative Stress In Immobilization and Physimentioning
confidence: 71%
“…Data from animals, and more recently from humans, indicate that immobilization increases O 2 -and H 2 O 2 emissions in skeletal muscle [52][53][54][55][56]. Mitochondria contributes to muscle ROS production during immobilization [52, [54][55][56], but other studies highlight that XO plays also an important role [57,58].…”
Section: Skeletal Muscle Oxidative Stress In Immobilization and Physimentioning
confidence: 99%
“…Increased ROS generation is a significant component of UV-B-induced damage to cells (Gniadecki et al, 2001;Ichihashi et al, 2003;Paz et al, 2008;Birch-Machin and Swalwell, 2010). Excess ROS can have detrimental effects on muscle function and metabolism, thereby impacting performance of animals under natural conditions (Kuwahara et al, 2010;Gram et al, 2015). However, the mechanistic pathways by which UV-B-induced ROS affect animal performance remain unsolved.…”
Section: Introductionmentioning
confidence: 99%